Economic Feasibility and Nutritional Security of Tribal Farmers through Grow Bag-based Organic Vegetables Production in Chhattisgarh Plain Agro-climatic Zone, Madhya Pradesh - Thakur, R. K.; Rai, S. K.; Bhalawe, S.; Shrivastava, A. K.; Lodhi, A. S.; Sarvade, S. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted in January-December, 2023 under the ICAR-supported Tribal Sub Plan (TSP) at 150 tribal farmers across the Baihar, Paraswada, and Birsa developmental blocks of the Balaghat district, Madhya Pradesh, India to assess the impact of grow bag-based organic vegetable cultivation on productivity, profitability, and nutritional well-being among tribal communities in the Chhattisgarh Plain Agro-climatic Zone of Madhya Pradesh. Farmers were provided with complete input kits, including grow bags, drip irrigation setups, enriched organic nutrients, and seedlings of four vegetable crops i.e. tomato, brinjal, cabbage, and chili. In comparison to traditional farming, the grow bag system showed marked improvements. Average yields per 25 bags reached 356 kg for tomato, 230 kg for brinjal, 40 kg for cabbage, and 33 kg for chili, nearly doubling the output from existing conventional methods. Economic analysis revealed a sharp rise in the benefit–cost ratio from 1.40 (farmers' practice) to 2.88 under the improved package. Extension and technology gap studies highlighted critical knowledge shortfalls, emphasizing the value of focused capacity-building. Beyond yield and income, the initiative enhanced household dietary diversity and vegetable intake frequency. Largely, the intervention demonstrated high adaptability and scalability, offering a sustainable, space-efficient model for year-round vegetable cultivation, improved nutrition, and livelihood security in resource-poor tribal settings. Thus, the grow bag based organic vegetable production technology significantly superior from the traditional methods.